Aluminum precursor and thin film forming method using the same, aluminum precursor manufacturing method, and memory element manufacturing method

A novel aluminum precursor, formed by mixing trimethylaluminum with ethyl methyl sulfide or ethyl propyl ether, addresses the challenge of uniform thin film deposition in 3D NAND Flash technology, ensuring improved step coverage and safety while reducing flammability.

JP7619661B2Active Publication Date: 2025-01-22EGTM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023078213
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-16
Filing Date
2023-05-10
Publication Date
2025-01-22
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

The challenge in 3D NAND Flash technology is forming a uniform thin film with excellent step coverage on a three-dimensional structure with a large aspect ratio, particularly due to the limitations of traditional precursors like trimethylaluminum, which are flammable and pose safety risks, and result in non-uniform thin film deposition.

Method used

A new aluminum precursor is formed by mixing trimethylaluminum with ethyl methyl sulfide or ethyl propyl ether in specific molar ratios, along with a surface protection substance, to enhance vaporization characteristics, thermal safety, and uniform thin film formation.

Benefits of technology

The new precursor allows for the formation of a highly uniform thin film with improved step coverage, reduced flammability, and enhanced electrical characteristics by preventing non-uniform deposition, even in ultra-high stacked structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619661000012
    Figure 0007619661000012
  • Figure 0007619661000013
    Figure 0007619661000013
  • Figure 0007619661000014
    Figure 0007619661000014
Patent Text Reader

Abstract

To provide an aluminum precursor that is superior in vaporization properties and heat safety, a method for forming a thin layer using the same, a method for manufacturing the aluminum precursor, and a method for manufacturing a memory device.SOLUTION: A method for manufacturing an aluminum precursor includes mixing 1 to 3 moles of an aluminum compound represented by the following Chemical Formula 3 with 1 to 3 moles of compounds such as ethyl methyl sulfide and ethyl propyl ether. R1, R2 and R3 are different from each other and selected from a hydrogen atom, a C1-6 alkyl group, a C1-6 dialkyl amine, a C1-6 cycloamine group and a halogen element.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum precursor, a thin film formation method using the same, a method for manufacturing an aluminum precursor, and a method for manufacturing a memory element, and more specifically, to an aluminum precursor which is safe, has easy control over the thickness of the thin film, and has excellent step coverage characteristics, and a thin film formation method using the same, a method for manufacturing an aluminum precursor, and a method for manufacturing a memory element. [Background technology]

[0002] The traditional 2D NAND Flash process has reached its technical limit due to the high integration density in a small area, which leads to increased interference and leakage between cells. To overcome these shortcomings, 3D NAND Flash technology has emerged, which stacks cells vertically.

[0003] The advantage of 3D NAND Flash, which includes multiple stacks, is that it can greatly reduce interference between cells, improving characteristics, and increasing the number of stacks can expand data capacity and reduce costs. This allows for more than twice the write speed, more than 10 times the durability, and half the power consumption compared to conventional NAND memory elements.

[0004] However, in ultra-high stacking of 90 or more layers, as the height increases, it becomes more difficult to secure a uniform thin film on the sidewall, and limitations arise such as differences in characteristics between the top and bottom cells. Therefore, there is a growing demand for a manufacturing method that can form a thin film of uniform thickness with excellent step coverage on 3D structures with a large aspect ratio.

[0005] In addition, thin films containing aluminum play a very important role in semiconductor device manufacturing. Thin films containing aluminum include aluminum film, aluminum nitride film, aluminum carbonitride film, aluminum oxide film, aluminum oxynitride film, etc., and aluminum nitride film and aluminum oxide film play important roles as passivation layers, interlayer insulating films, capacitor dielectric layers, etc.

[0006] Currently, trimethylaluminum (TMA) or triisobutylaluminum is used as a precursor for depositing aluminum-containing thin films. However, these substances are explosively flammable and require considerable care when handling them. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide an aluminum precursor having excellent vaporization characteristics and thermal stability, a method for forming a thin film using the same, a method for manufacturing an aluminum precursor, and a method for manufacturing a memory device.

[0008] Another object of the present invention is to provide an aluminum precursor having good step coverage, a method for forming a thin film using the same, a method for manufacturing an aluminum precursor, and a method for manufacturing a memory device.

[0009] Yet another object of the present invention is to provide an aluminum precursor capable of forming a thin film of extremely uniform thickness and facilitating thickness adjustment, a thin film forming method using the same, a method for manufacturing an aluminum precursor, and a method for manufacturing a memory element.

[0010] Other objects of the present invention will become more apparent from the following detailed description. [Means for solving the problem]

[0011] According to one embodiment of the present invention, a method for producing an aluminum precursor includes: 1-3 moles of trimethylaluminum and 1-3 moles of ethyl methyl sulfide or ethyl propyl ether It is formed by mixing

[0015] The aluminum precursor comprises: The above Ethyl methyl sulfide and The above Trimethylaluminum and At a molar ratio of 1:1 or 2:1 It can be formed by mixing.

[0016] The aluminum precursor comprises: The above Ethyl propyl ether The above Trimethylaluminum and At a molar ratio of 2:1 It can be formed by mixing.

[0017] According to one embodiment of the invention, the aluminum precursor comprises: The reaction was carried out by a mixture of 1-3 moles of trimethylaluminum and 1-3 moles of ethyl methyl sulfide or ethyl propyl ether. is formed.

[0021] According to one embodiment of the present invention, a thin film formation method includes a precursor supply step of supplying the aluminum precursor into a chamber in which a substrate is placed; a step of purging the inside of the chamber; and a thin film formation step of supplying a reactant into the chamber and reacting it with the precursor to form a thin film.

[0022] The thin film can be aluminum oxide, aluminum nitride, or aluminum sulfide.

[0023] According to one embodiment of the present invention, a method for forming a thin film using a surface protective material includes a metal precursor supplying step of supplying a metal precursor into a chamber in which a substrate is placed and adsorbing the metal precursor onto the substrate; a step of purging the interior of the chamber; and a thin film forming step of supplying a reactant into the chamber to react with the adsorbed metal precursor to form a thin film, and the method includes a surface protective material supplying step of supplying a surface protective material and adsorbing it onto the substrate before the thin film forming step; and a step of purging the interior of the chamber, and the metal precursor is A mixture of 1-3 moles of trimethylaluminum and 1-3 moles of ethyl methyl sulfide or ethyl propyl ether. .

[0027] The metal precursor comprises: The above Ethyl methyl sulfide and the trimethylaluminum in a molar ratio of 1:1 or 2:1, or The above Ethyl Propyl Ether Ru and the above Trimethylaluminum and At a molar ratio of 2:1 It can be formed by mixing.

[0028] The surface protective material may be represented by the following <Chemical Formula 4>.

[0029] [ka] In the <Chemical Formula 4>, n is each independently an integer of 0 to 6, X is O or S, R1 to R3 are independently an alkyl group having 1 to 6 carbon atoms, and R4 is selected from hydrogen, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, and an alkylthio group having 1 to 6 carbon atoms.

[0030] The thin film can be either aluminum oxide, aluminum nitride, or aluminum sulfide.

[0031] The thin film formation method can proceed at a temperature of 50 to 700°C.

[0032] According to an embodiment of the present invention, a method for manufacturing a volatile memory device may include the thin film forming method.

[0033] According to an embodiment of the present invention, a method for manufacturing a non-volatile memory device may include the thin film forming method. Effect of the Invention

[0034] According to one embodiment of the present invention, a thin film with good step coverage can be formed.

[0035] The surface protective material behaves similarly to the metal precursor during processing, being densely adsorbed on the top (or inlet side) of the high aspect ratio structure and sparsely adsorbed on the bottom (or inner side) to prevent the metal precursor from adsorbing in subsequent processes, thus allowing the metal precursor to be uniformly adsorbed within the structure.

[0036] In particular, with its excellent step coverage, it is possible to form a highly pure thin film without impurities while reducing the difference in cell characteristics between the top and bottom layers even in an ultra-high stacked structure, thereby improving the electrical characteristics and reliability of the device.

[0037] In addition, it is possible to prevent the phenomenon of spontaneous combustion of the aluminum precursor due to exposure to air, and it has excellent thermal safety and can be transported to the substrate surface in a stable gas phase.

[0038] In particular, by being introduced together with a surface protection material to maximize its effect, the deposition thickness per cycle can be minimized, facilitating thickness control, and the deposited thin film can ensure excellent uniformity and step coverage. [Brief description of the drawings]

[0039] [Figure 1] 1 is a 1H-NMR graph of precursor X1 according to Example 1 of the present invention. [Diagram 2] 1 is a 1H-NMR graph of precursor X2 according to Example 2 of the present invention. [Diagram 3] 1H-NMR graph of precursor Y2 according to Example 3 of the present invention. [Figure 4] 1 is a graph showing differential scanning calorimetry (DSC) test results and thermogravimetric analysis (TGA) test results for Examples 1 to 3. [Diagram 5] 1 is a graph showing differential scanning calorimetry (DSC) test results and thermogravimetric analysis (TGA) test results for Examples 1 to 3. [Figure 6] 1 is a graph showing differential scanning calorimetry (DSC) test results and thermogravimetric analysis (TGA) test results for Examples 1 to 3. [Figure 7] 1 is a graph showing differential scanning calorimetry (DSC) test results and thermogravimetric analysis (TGA) test results for Examples 1 to 3. [Figure 8] 1 is a graph showing differential scanning calorimetry (DSC) test results and thermogravimetric analysis (TGA) test results for Examples 1 to 3. [Figure 9] 1 is a graph showing differential scanning calorimetry (DSC) test results and thermogravimetric analysis (TGA) test results for Examples 1 to 3. [Figure 10] 4 is a photograph showing the results of an outdoor exposure test for Examples 1 to 3. [Figure 11]1 is a graph showing the weight change after exposure to the outside air for Examples 2 and 3. [Figure 12] FIG. 1 is a schematic diagram comparing TMA with an embodiment of the present invention. [Figure 13] 1 is a graph showing GPC (Growth Per Cycle) of aluminum oxide films according to Comparative Example 1 and Example 2 of the present invention as a function of process temperature. [Figure 14] 1 is a flow chart that illustrates a thin film formation method according to an embodiment of the present invention. [Figure 15] 4 is a graph that illustrates a schematic representation of a dispensing cycle according to an embodiment of the present invention. [Figure 16] 1 is a graph showing the weight change after exposure to the outside air for Examples 2 and 4. [Figure 17] 1 is a graph showing the results of mixing a precursor TMA corresponding to Comparative Example 1-1 and a surface protective material TMOF in a liquid phase. [Figure 18] 1 is a graph showing the results of mixing a precursor TMA-THF corresponding to Example 2-1 and a surface protective material TMOF in a liquid phase. [Figure 19] The GPC (Growth Per Cycle) of aluminum oxide films with increasing precursor feeding time at the same deposition temperature is shown. [Figure 20] The GPC (Growth Per Cycle) of aluminum oxide films with increasing precursor feeding time at the same deposition temperature is shown. [Figure 21] 1 is a graph showing an XPS depth profile for analyzing the surface of an aluminum oxide film according to an embodiment of the present invention. [Figure 22] 1 shows a result of confirming step coverage when an aluminum oxide film according to an embodiment of the present invention is deposited on a patterned wafer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] Preferred embodiments of the present invention will now be described in more detail with reference to the accompanying Figures 1 to 22. The embodiments of the present invention may be modified in various forms, and the scope of the present invention should not be construed as being limited to the embodiments described below. These embodiments are provided to explain the present invention in more detail to those skilled in the art to which the invention pertains. Therefore, the shape of each element shown in the drawings may be exaggerated to emphasize a clearer description.

[0041] According to one embodiment of the present invention, a thin film formation method includes a precursor supply step of supplying an aluminum precursor into a chamber in which a substrate is placed; a step of purging the inside of the chamber; and a thin film formation step of supplying a reactant into the chamber and reacting it with the precursor to form a thin film.

[0042] The precursor supplying step and the thin film forming step may be carried out at a temperature of 50 to 700°C.

[0043] The thin film can be either aluminum oxide, aluminum nitride, or aluminum sulfide.

[0044] According to one embodiment of the present invention, a method for producing an aluminum precursor is formed by mixing 1 to 3 moles of a compound represented by the following <Chemical Formula 1> or the following <Chemical Formula 2> and 1 to 3 moles of a compound represented by the following <Chemical Formula 3>.

[0045] [ka] In the above <Chemical Formula 1>, X is O or S, and R1 and R2 are each independently selected from an alkyl group having 1 to 8 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group having 6 to 12 carbon atoms.

[0046] [ka] In the above <Chemical Formula 2>, X is O or S, n = 1 to 5, and R1 to R4 are each independently selected from a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group having 6 to 12 carbon atoms.

[0047] [ka] In the <Chemical Formula 3>, R1, R2 and R3 are different from each other and are each independently selected from a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a dialkylamine group having 1 to 6 carbon atoms, a cycloamine group having 1 to 6 carbon atoms, or a halogen element.

[0048] The aluminum precursor may be formed by mixing ethyl methyl sulfide and trimethyl aluminum.

[0049] The aluminum precursor may be formed by mixing ethyl propyl ether and trimethyl aluminum.

[0050] Example 1 In a glove box at room temperature, 5.28 g (0.069 mol) of ethyl methyl sulfide was added to a 500 ml round flask, and 5 g (0.069 mol) of trimethylaluminum was added very slowly to obtain precursor X1.

[0051] FIG. 1 is a 1H-NMR graph of precursor X1 according to Example 1 of the present invention, showing the NMR spectrum of Example 1 / ethyl methyl sulfide / trimethylaluminum.

[0052] The peaks at δ=2.19 ppm, 1.76 ppm, and 1.20 ppm, which are due to chemical shifts caused by ethyl methyl sulfide, did not change in shape even after the formation of precursor X1, and shifted to 1.92 ppm, 1.41 ppm, and 0.69 ppm, respectively.

[0053] It can be confirmed that the peak of chemical migration δ = -0.36 ppm derived from trimethylaluminum also moves finely without changing its shape after the formation of precursor X1 to form a stable precursor. The integral ratio of Ha (9H):Hb (3H) is about 9:2.8, and it can be confirmed that one molecule of ethyl methyl sulfide forms the precursor.

[0054] Example 2: Preparation of TMA-EMS In a glove box at room temperature, 10.56 g (0.139 mol) of ethyl methyl sulfide was added to a 500 ml round flask, and 5 g (0.069 mol) of trimethylaluminum was added very slowly to obtain precursor X2 (TMA-EMS).

[0055] FIG. 2 is a 1H-NMR graph of precursor X2 according to Example 2 of the present invention, showing the NMR spectrum of Example 2 / ethyl methyl sulfide / trimethylaluminum.

[0056] The peaks at δ=2.19 ppm, 1.76 ppm, and 1.20 ppm, which are due to chemical shifts caused by ethyl methyl sulfide, did not change in shape even after the formation of precursor X2, and shifted to 2.05 ppm, 1.58 ppm, and 0.85 ppm, respectively.

[0057] The peaks at δ=2.19 ppm, 1.76 ppm, and 1.20 ppm, which were derived from EMS, did not change in shape even after the precursor was formed, and shifted to 2.05 ppm, 1.58 ppm, and 0.85 ppm, respectively, confirming the formation of stable substances.

[0058] It can also be confirmed that the peak of chemical migration δ = -0.36 ppm derived from trimethylaluminum does not change shape after the formation of precursor X2, but moves finely to form a stable precursor. The integral ratio of Ha (9H):Hb (3H) is about 9:5.7, and it can be confirmed that two molecules of ethyl methyl sulfide form the precursor.

[0059] Example 3 In a glove box at room temperature, 12.23 g (0.139 mol) of ethyl propyl ether was added to a 500 ml round flask, and 5 g (0.069 mol) of trimethylaluminum was added very slowly to obtain precursor Y2.

[0060] FIG. 3 is a 1 H-NMR graph of precursor Y2 according to Example 3 of the present invention, showing the NMR spectrum of Example 3 / ethyl propyl ether / trimethylaluminum.

[0061] The peaks at δ=0.89 ppm, 1.12 ppm, and 1.55 ppm, which are attributable to ethyl propyl ether, did not change in shape even after the formation of precursor Y2, and shifted to 0.65 ppm, 0.89 ppm, and 1.35 ppm, respectively.

[0062] It can be confirmed that the peak of chemical migration δ = -0.36 ppm derived from trimethylaluminum also moves finely without changing its shape after the formation of precursor Y2 to form a stable precursor. The integral ratio of Ha (9H):Hb (3H) is about 9:5.7, and it can be confirmed that two molecules of ethyl propyl ether form the precursor.

[0063] - Thermal analysis 4 to 9 are graphs showing the results of differential scanning calorimetry (DSC) tests and thermogravimetry (TGA) tests for Examples 1 to 3. Differential scanning calorimetry (DSC) tests and thermogravimetry (TGA) tests were carried out for X1, X2, and Y2 obtained in Examples 1 to 3, and the thermal analysis test conditions for measuring the thermal decomposition temperature in each test are as follows. Transport gas: Argon (Ar) gas Transport gas flow rate: 200ml / min Heating profile: Heat from 30℃ to 500℃ at a rate of 10℃ / min.

[0064] The thermal decomposition temperature in the DSC test was determined as the temperature at which the heat flow suddenly increased during heating on the DSC thermogram.

[0065] Referring to Table 1 below, both X1 and X2 have excellent vaporization characteristics with residual components of less than 0.1%, which means that they do not leave impurities in the thin film. In addition, the decomposition temperature is over 340℃, and compared to the use of TMA alone, the organic molecules effectively block the Al-Al interactions between TMA, showing improved thermal stability with a high decomposition temperature, and it can be confirmed that they can be delivered to the substrate surface in a stable vapor phase.

[0066] [Table 1]

[0067] In addition, since the vaporization characteristics of X2 are further improved despite the molecular weight being larger than that of X1, it is believed that the two organic molecules effectively block the Al-Al interaction between TMA, making X2 more suitable for use in terms of stability.

[0068] It was also confirmed that Y2 has the vaporization properties required for use as an ALD precursor due to the bimolecular blocking effect, with a decomposition temperature of over 344°C, which is higher than that of TMA alone, demonstrating improved thermal stability and the ability to be transported to the substrate surface in a stable gas phase.

[0069] - Outdoor exposure test Figure 10 is a photograph showing the results of the outdoor exposure test for Examples 1 to 3. The same amounts of X1, X2, and Y2 obtained in Examples 1 to 3 were exposed to room temperature / normal pressure. X1 ignited immediately when exposed to the pipette state, but X2 / Y2 only generated minute fumes and did not ignite. It can be confirmed that the flammability is extremely reduced in the atmosphere and that they do not ignite even in air. The reason why spontaneous combustion is suppressed in X2 / Y2 compared to X1 is thought to be the effect of forming a very stable substance by completely blocking the empty P orbital of Al by two molecules.

[0070] 11 is a graph showing the weight change after exposure to the outside air for Examples 2 and 3. When the same amount of X2 / Y2 was exposed to the outside air, the weight of Y2 rapidly decreased, completely solidified after 5 hours, and no further weight change occurred, whereas the weight loss rate of X2 was relatively slow, completely solidified after 7 hours, and no further weight change occurred.

[0071] In both cases, an oxidation reaction occurs, but it does not result in ignition, greatly increasing stability during handling and significantly reducing the risk of accidents.

[0072] The air exposure tests in Figures 10 and 11 are considered to be similar to the chemical reaction of precursors adsorbing on a surface. During air exposure, the precursors undergo a chemical reaction in which the Al-C bonds are broken and replaced with Al-O bonds as they react with HO in the air, which is very similar to the reaction in which the precursors meet the -OH* terminated surface of an oxide film and the ligands fall off and are adsorbed.

[0073] From the results of Figures 10 and 11, it can be seen that in both the X2 and Y2 precursors of the embodiment, the empty P orbitals of Al are completely blocked with organic materials, and the oxidation reaction occurs very slowly even when exposed to the atmosphere, greatly reducing the reactivity. The schematic diagram of Figure 12 confirms the low reactivity of the completely blocked precursor.

[0074] Furthermore, the diameter of the X2 precursor is approximately 6.6 Å, which is significantly larger than the diameter of TMA, which is 4.1 Å. This not only further reduces the accessibility of the Al center of the X2 precursor to the surface -OH*, but also reduces the deposition thickness per cycle due to greater steric hindrance when several adsorbed precursors are present on the surface. This can be confirmed by the deposition results using the X2 precursor in Figure 13.

[0075] Similarly, the X2 and Y2 precursors have reduced reactivity with the -OH* terminating groups on the surface, which reduces the sticking coefficient and increases diffusion at the surface, resulting in the formation of a uniform film, ultimately improving uniformity and step coverage.

[0076] - Comparative example 1: TMA deposition results An aluminum oxide film was formed on a silicon substrate by the ALD process, the ALD process temperature was 250-400℃, and O3 gas was used as the reactant.

[0077] The aluminum oxide film formation process by the ALD process is as follows, and the following steps were carried out as one cycle. 1) Using Ar as a carrier gas, the aluminum precursor TMA (Trimethylaluminium) was supplied to the reaction chamber at room temperature, and the aluminum precursor was adsorbed onto the substrate. 2) Supply Ar gas into the reaction chamber to remove any unadsorbed aluminum precursor or by-products. 3) O3 gas is supplied to the reaction chamber to form a monolayer. 4) Ar gas is supplied into the reaction chamber to remove unreacted materials or by-products.

[0078] The thickness of the aluminum oxide film obtained by the above process was measured, and the thickness of the aluminum oxide film obtained per cycle of the ALD process was about 0.9 Å / cycle at 250~400℃.

[0079] 13 is a graph showing the GPC (Growth Per Cycle) of aluminum oxide films according to Comparative Example 1 and Example 2 of the present invention versus process temperature. As shown in FIG. 13, ideal ALD behavior was shown with almost no change in GPC with increasing substrate temperature within the substrate temperature range of 250 to 400°C. Assuming that the total thickness of the dielectric film in the ZrO2 / Al2O3 / ZrO2 composite dielectric film of a DRAM is 50 Å and the Al2O3 of Comparative Example 1 is used for about 3 cycles, the EOT of the dielectric film is 5.93 Å.

[0080] Example 2: TMA-EMS deposition results An aluminum oxide film was formed on a silicon substrate using precursor X2 according to Example 2 of the present invention. The aluminum oxide film was formed in the same manner as in Comparative Example 1, except that the precursor was changed.

[0081] The thickness of the aluminum oxide film obtained by the above procedure was measured, and the thickness of the aluminum oxide film obtained per cycle of the ALD process was about 0.7 Å / cycle at 250-400°C.

[0082] 13, ideal ALD behavior is shown with almost no GPC change accompanying an increase in substrate temperature within the range of 250 to 400°C, and a reduction effect of approximately 20% is shown compared to Comparative Example 1. Assuming that the total thickness of the dielectric film in the ZrO2 / Al2O3 / ZrO2 composite dielectric film of a DRAM is 50 Å and the Al2O3 of Comparative Example 1 is used for about three cycles, the EOT of the dielectric film is 5.72 Å, and a sculling down of approximately 4% can be achieved compared to Comparative Example 1.

[0083] Meanwhile, in the conventional precursor-only process, in a high aspect ratio structure, the thin film is not uniform, with the upper part (or inlet side) being thicker and the lower part (or inner side) being thinner, resulting in poor step coverage.

[0084] However, the surface protection material described below behaves like a metal precursor and adsorbs more densely to the top of the structure than the bottom, preventing the subsequent metal precursor from adsorbing, thereby enabling the formation of a thin film of uniform thickness within the structure.

[0085] 14 is a flow chart that illustrates a thin film formation method according to an embodiment of the present invention, and FIG. 15 is a graph that illustrates a supply cycle according to an embodiment of the present invention. A substrate is loaded inside a process chamber, and the following ALD process conditions are adjusted. The ALD process conditions may include substrate or process chamber temperature, chamber pressure, and gas flow rates, and the temperature is 50-700°C.

[0086] The substrate is exposed to a surface protection material supplied inside the chamber, and the surface protection material is adsorbed on the surface of the substrate. The surface protection material behaves similarly to the metal precursor during the process, being adsorbed in high density on the top (or inlet side) and in low density on the bottom (or inside) in a high aspect ratio structure, preventing the metal precursor from adsorbing in the subsequent process.

[0087] Specifically, the metal precursor is formed by mixing 1 to 3 moles of a compound represented by the following <Chemical Formula 1> or the following <Chemical Formula 2> and 1 to 3 moles of a compound represented by the following <Chemical Formula 3>.

[0088] [ka] In the above <Chemical Formula 1>, X is O or S, and R1 and R2 are each independently selected from an alkyl group having 1 to 8 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group having 6 to 12 carbon atoms.

[0089] [ka] In the above <Chemical Formula 2>, X is O or S, n = 1 to 5, and R1 to R4 are each independently selected from a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group having 6 to 12 carbon atoms.

[0090] [ka] In the above <Chemical Formula 3>, R1, R2 and R3 are different from each other and are each independently selected from a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a dialkylamine group having 1 to 6 carbon atoms, a cycloamine group having 1 to 6 carbon atoms, or a halogen element.

[0091] The metal precursor can also be formed by mixing ethyl methyl sulfide, ethyl propyl ether, or tetrahydrofuran with trimethylaluminum.

[0092] In addition, the surface protective material can be represented by the following <Chemical Formula 4>.

[0093] [ka] In the <Chemical Formula 4>, n is independently an integer of 0 to 6, X is O or S, R1 to R3 are independently an alkyl group having 1 to 6 carbon atoms, R4 is hydrogen, It is selected from an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, and an alkylthio group having 1 to 6 carbon atoms.

[0094] Thereafter, a purge gas (eg, an inert gas such as Ar) is supplied into the chamber to remove or purify any unadsorbed surface protective material or by-products.

[0095] The substrate is then exposed to the metal precursor supplied inside the chamber, and the metal precursor is adsorbed onto the surface of the substrate. At this time, the precursor supply process proceeds at 50 to 700°C.

[0096] For example, the above-mentioned surface protective material is adsorbed more densely from the top to the bottom of the structure, and the metal precursor cannot be adsorbed at the position where the surface protective material is adsorbed. That is, the conventional metal precursor was adsorbed more densely from the top to the bottom of the structure and showed a high density, but as in this embodiment, the surface protective material is densely adsorbed at the top of the structure and prevents the adsorption of the metal precursor, so that the metal precursor can be uniformly adsorbed at the top / bottom of the structure without being over-adsorbed at the top of the structure, and the step coverage of the thin film described later can be improved.

[0097] Thereafter, a purge gas (eg, an inert gas such as Ar) is supplied into the chamber to remove or purify any unadsorbed metal precursor or by-products.

[0098] The substrate is then exposed to a reactive material supplied inside the chamber to form a thin film on the surface of the substrate. The reactive material reacts with the metal precursor layer to form a thin film, and the reactive material is O3, O2, or H2O gas, and a metal oxide film can be formed through the reactive material. At this time, the reactive material oxidizes the adsorbed surface protection material, and separates and removes it from the surface of the substrate. The thin film formation process proceeds at 50 to 700°C, and the thin film can be any of aluminum oxide, aluminum nitride, or aluminum sulfide.

[0099] Thereafter, a purge gas (eg, an inert gas such as Ar) is supplied into the chamber to remove or purify any unadsorbed surface protective substances / unreacted materials or by-products.

[0100] On the other hand, although it has been described that the surface protective material is supplied prior to the metal precursor, in contrast to this, the surface protective material may be supplied after the metal precursor, or before or after the metal precursor.

[0101] Comparative Example 1-1: Deposition results using TMA and surface protection material TMOF An aluminum oxide film was formed on a silicon substrate using TMOF (Trimethyl orthoformate) of the above formula 4 as a surface protective material. The aluminum oxide film was formed in the same manner as in Comparative Example 1, except for using the surface protective material.

[0102] The aluminum oxide film formation process by the ALD process is as follows, and the following steps were carried out as one cycle. 1) A surface protection material is supplied into the reaction chamber and adsorbed onto the substrate. 2) Ar gas is supplied into the reaction chamber to remove unadsorbed surface protective materials or by-products. 3) Using Ar as a carrier gas, the aluminum precursor is supplied to the reaction chamber at room temperature, and the aluminum precursor is adsorbed onto the substrate. 4) Supply Ar gas into the reaction chamber to remove any unadsorbed aluminum precursor or by-products. 5) O3 gas is supplied to the reaction chamber to form a monolayer. 6) Ar gas is supplied into the reaction chamber to remove unreacted materials or by-products.

[0103] Example 2-1: Vapor deposition results using TMA-EMS and surface protection material TMOF An aluminum oxide film was formed on a silicon substrate using TMOF (Trimethyl orthoformate) of the above <Chemical Formula 4> as a surface protective material. The aluminum oxide film was formed in the same manner as in Comparative Example 1-1, except that the precursor was changed.

[0104] Example 4: Preparation and deposition results of TMA-THF The THF (tetrahydrofuran) according to the present invention and TMA were mixed to form an Al precursor. In a glove box at room temperature, 10 g (0.139 mol) of tetrahydrofuran was added to a 500 ml round flask, and 10 g (0.139 mol) of trimethylaluminum was added very slowly to obtain the precursor TMA-THF.

[0105] The peaks at δ=3.57 ppm and 1.42 ppm due to chemical shifts caused by EMS did not change in shape even after the precursor was formed, and shifted to 3.35 ppm and 0.96 ppm, respectively, confirming the formation of stable substances.

[0106] The aluminum oxide film was formed on a silicon substrate using the produced TMA-THF. The aluminum oxide film was formed in the same manner as in Comparative Example 1, except that the precursor was changed.

[0107] Example 4-1: Vapor deposition results using TMA-THF and surface protection material TMOF An aluminum oxide film was formed on a silicon substrate using TMOF (trimethyl orthoform) of the above formula 4 as a surface protective material. Except for changing the precursor, an aluminum oxide film was formed in the same manner as in Comparative Example 1-1.

[0108] - Outdoor exposure test 1 is a graph showing the weight change after exposure to the outside air for Examples 2 and 4. It was confirmed that both precursors had extremely reduced flammability in the atmosphere and existed in a liquid state without igniting even in air. The reason why spontaneous combustion is suppressed can be considered as the effect of forming a very stable substance by completely blocking the empty P orbitals of Al with organic molecules.

[0109] For both precursors, it can be confirmed that the weight loss is very slow and the oxidation reaction rate is slow. The air exposure test is considered to be similar to the chemical reaction of the precursor adsorbing on the surface. During air exposure, the precursor undergoes a chemical reaction in which the Al-C bond is broken by reacting with H2O in the air and replaced with an Al-O bond, which is very similar to the reaction in which the precursor meets the -OH* terminated surface of the oxide film and the ligand falls off and is adsorbed. Therefore, it can be inferred that the decrease in reactivity of the Al precursor in the air also occurs in the surface reaction.

[0110] 17 is a graph showing the result of mixing the precursor TMA corresponding to Comparative Example 1-1 and the surface protective material TMOF in the liquid phase. In order to mimic the reaction with the surface protective material on the surface, the precursor corresponding to Comparative Example 1-1 and the surface protective material were mixed in liquid form.

[0111] One equivalent of trimethyl aluminum was slowly added to six equivalents of TMOF (trimethyl orthoformate), and the mixture was thoroughly stirred. The peaks of the mixture were assigned by 1 H NMR (C6D6) analysis. TMOF,HC(OCH3)2:δ4.82(s),3.12(s) (CH3)2Al(OCH3):δ3.05(s),-0.57(s) CH3CH(OCH3)2:δ4.42(m),3.10(s),1.17(d)

[0112] By adding an excess of TMOF (trimethyl orthoformate), the peaks δ4.82 and 3.12 were confirmed, which were caused by the unreacted surface protective material, and the product peaks formed by the ligand substitution reaction between the precursor and the surface protective material were confirmed. The peak δ-0.36, which was caused by trimethyl aluminum before the reaction, completely disappeared, confirming that the reaction had been completed.

[0113] 18 is a graph showing the result of mixing the precursor TMA-THF corresponding to Example 4-1 and the surface protective material TMOF in the liquid phase. The precursor and the surface protective material corresponding to Example 4-1 were mixed in the liquid phase.

[0114] One equivalent of TMA-THF was slowly added to one equivalent of TMOF (trimethyl orthoformate) and thoroughly stirred. The mixed solution was subjected to 1H NMR (C6D6) analysis and peak assignment. TMOF,HC(OCH3)2:δ4.82(s),3.12(s) TMA-THF:δ3.43(m),δ1.16(m),-0.39(s) (CH3)2Al(OCH3):δ3.05(s),-0.57(s) CH3CH(OCH3)2:δ4.42(m),3.10(s),1.17(d)

[0115] The product peak formed by the ligand substitution reaction between the precursor and the surface protective material was confirmed, as in the previous results. However, unlike the trimethyl aluminum precursor which disappeared after it had all reacted, the unreacted TMA-THF and trimethyl orthoformate peaks were confirmed. This can also be interpreted as the reactivity of TMA-THF with the surface protective material becoming very low, and it is expected that the surface reaction during deposition will lead to a decrease in the sticking coefficient and an increase in diffusion on the surface, improving the step coverage for existing precursors.

[0116] The following Table 2 shows the GPC (Growth Per Cycle) of the aluminum oxide films according to the comparative example of the present invention and Examples 2 and 4.

[0117] [Table 2]

[0118] Comparing the GPC of the Al precursor without a surface protective material, it was confirmed that the GPC of Examples 2 and 4 decreased by 26% and 23%, respectively, compared to the use of TMA alone. This can be interpreted as a decrease in the reactivity of the precursor due to the Al blocking effect, and a decrease in the accessibility of the Al center and surface -OH* due to an increase in size relative to TMA.

[0119] This reduced reactivity with the surface -OH* termination group leads to a reduced sticking coefficient and increased diffusion at the surface, resulting in the formation of a more uniform film, ultimately improving uniformity and step coverage.

[0120] It can be seen that the GPC reduction of the Al precursor using the surface protective material is further maximized. In Comparative Example 1-1, the reduction rate when only the surface protective material is applied is 30%, whereas in Example 4-1, when both the TMA-THF precursor and the surface protective material of the present invention are applied, the reduction rate is significantly increased to 70%.

[0121] Assuming that the total thickness of the dielectric film in the ZrO2 / Al2O3 / ZrO2 composite dielectric film of a DRAM is 50 Å and that the Al2O3 of Example 2-1 is used for approximately three cycles, the EOT of the dielectric film is 5.21 Å, and a sculling down of approximately 12% can be achieved compared to the use of TMA alone in Comparative Example 1.

[0122] 19 and 20 show the GPC (Growth Per Cycle) of aluminum oxide films with increasing precursor feeding time at the same deposition temperature.

[0123] In the comparative example of Figure 19, the GPC with the surface protective material applied increases continuously as the precursor feeding time increases, and the saturation characteristics are not good and it is not easy to control. On the other hand, the GPC with the surface protective material applied in the example of Figure 20 has a very low GPC compared to the existing precursor only process, and there is very little change in GPC even with an increase in the precursor feeding time, so it shows saturation characteristics and is suitable for the ALD process.

[0124] 21 is a graph showing an XPS depth profile for analyzing the surface of an aluminum oxide film according to an embodiment of the present invention. The carbon concentration in the thin film was 0%, forming a thin film without impurities.

[0125] 22 shows the results of checking step coverage when an aluminum oxide film according to an embodiment of the present invention is deposited on a patterned wafer. It was confirmed that excellent characteristics were shown with a step coverage of 100% in all examples.

[0126] In conclusion, by applying the Al precursor and surface protection material of the present invention, a high GPC reduction effect can be obtained, which not only allows precise thickness control and excellent step coverage, but also improves the electrical properties and reliability of devices. In addition, it is possible to form a thin film with high purity and without impurities, thinner than one monolayer thickness obtained by the existing ALD process.

[0127] Although the present invention has been described in detail with reference to the embodiments, other embodiments are possible, and therefore the technical spirit and scope of the following claims are not limited to the embodiments.

Claims

1. A method for producing an aluminum precursor, which comprises mixing 1 to 3 moles of trimethylaluminum with 1 to 3 moles of ethyl methyl sulfide or 1 to 3 moles of ethyl propyl ether.

2. 2. The method of claim 1, wherein the aluminum precursor is formed by mixing the ethyl methyl sulfide and the trimethyl aluminum in a molar ratio of 1:1 or 2:

1.

3. 2. The method of claim 1, wherein the aluminum precursor is formed by mixing the ethyl propyl ether and the trimethylaluminum in a molar ratio of 2:

1.

4. An aluminum precursor comprising a mixture of 1 to 3 moles of trimethylaluminum and 1 to 3 moles of ethyl methyl sulfide or ethyl propyl ether.

5. A precursor supply step of supplying the aluminum precursor according to claim 4 into a chamber in which a substrate is placed; purging the interior of the chamber; and The method includes the step of supplying a reactant into the chamber and reacting the reactant with the precursor to form a thin film.

6. 6. The method for forming a thin film according to claim 5, wherein the thin film is any one of aluminum oxide, aluminum nitride, and aluminum sulfide.

7. The method for forming a thin film according to claim 5, wherein the thin film forming method proceeds at a temperature of 50 to 700°C.

8. A method for manufacturing a volatile memory element, comprising the thin film forming method according to claim 5.

9. A method for manufacturing a non-volatile memory element, comprising the thin film forming method according to claim 5.

10. In a thin film formation method using a surface protection material, a metal precursor supplying step of supplying a metal precursor into a chamber in which a substrate is placed and adsorbing the metal precursor on the substrate; purging the interior of the chamber; and a thin film formation step of supplying a reactant into the chamber to react with the adsorbed metal precursor to form a thin film, The method further comprises, before the thin film forming process, a step of supplying a surface protective material and adsorbing the surface protective material on the substrate; purging the interior of the chamber, The method for forming a thin film using a surface protective material is characterized in that the metal precursor is an aluminum precursor made of a mixture of 1 to 3 moles of trimethylaluminum and 1 to 3 moles of ethyl methyl sulfide or ethyl propyl ether.

11. 11. The method of forming a thin film using a surface protective material according to claim 10, wherein the metal precursor is formed by mixing the ethyl methyl sulfide and the trimethyl aluminum in a molar ratio of 1:1 or 2:1, or by mixing the ethyl propyl ether and the trimethyl aluminum in a molar ratio of 2:

1.

12. 11. The method of claim 10, wherein the surface protective material is represented by the following formula 4: In the formula 4, n is an integer of 0 to 6, X is O or S, and R 1 ~R 3 are independently alkyl groups having 1 to 6 carbon atoms; R 4 is selected from hydrogen, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, and an alkylthio group having 1 to 6 carbon atoms.

13. 11. The method for forming a thin film using a surface protective material according to claim 10, wherein the thin film is any one of aluminum oxide, aluminum nitride, and aluminum sulfide.

14. 11. The method for forming a thin film using a surface protective material according to claim 10, wherein the thin film formation method proceeds at a temperature of 50 to 700.degree.

15. A method for manufacturing a volatile memory element, comprising the thin film formation method according to any one of claims 10 to 14.

16. A method for manufacturing a non-volatile memory element, comprising the thin film formation method according to any one of claims 10 to 14.

Citation Information

Patent Citations

  • Aluminum compound and forming method of aluminum-containing film using the same

    KR1020160101697A

  • Method of depositing thin films using protective material

    KR1020210059332A

  • Method for forming thin film using surface protection material

    WO2021141324A1